Realtime Achilles Ultrasound Thompson (RAUT) Test for the Evaluation and Diagnosis of Acute Achilles Tendon Ruptures. (January 2017) - Griffin, Matthew J.; Olson, Kirstina; Heckmann, Nathanael; Charlton, Timothy P.
Background: Acute complete Achilles tendon ruptures are commonly missed injuries. We propose the Realtime Achilles Ultrasound Thompson (RAUT) test, a Thompson test under ultrasound visualization, to aid in the diagnosis of these injuries. We hypothesized that RAUT testing would provide improved diagnostic characteristics compared with static ultrasound. Methods: Twenty-two consecutive patients with operatively confirmed acute Achilles tendon ruptures were prospectively evaluated with RAUT testing and static ultrasonography. RAUT video recordings and static ultrasound images from both ruptured and uninjured sides were randomized and graded by a group of novice reviewers and a group of expert attendings. From these observations, sensitivity, specificity, positive predictive value, and negative predictive value for RAUT and static ultrasound were calculated. In addition, κ interobserver coefficients were computed. Forty-seven novice reviewers and 11 foot and ankle attendings made a total of 4136 and 528 observations, respectively. Results: For static ultrasound, sensitivity and specificity were 76.8% and 74.8% for the novice reviewers and 79.6% and 86.4% for the attendings, respectively. For RAUT testing, sensitivity and specificity were 87.2% and 81.1% for the novice group and 86.4% and 91.7% for the attending group, respectively. The κ coefficient was 0.62 and 0.27 for novice and attending RAUT reviewers, indicating substantial and fair agreement, respectively, but only 0.46 and 0.12 for static ultrasonography, representing moderate and slight agreement, respectively. Conclusion: RAUT testing was a sensitive and specific test, providing a cost-effective adjunct to the clinical examination when diagnosing acute Achilles tendon ruptures. This test can be used by surgeons with minimal training in ultrasonography. Level of Evidence: Level II, diagnostic study.